KEPUASAN KERJA KARYAWAN: STUDI KASUS PADA TOKO SEMAT SARI BADUNG - Rangga, Samuel Umbu; Eka Putra, I Komang Trisna; Ni Made Puriati; I Wayan Sugiartana; Aditya Manggala RS (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2025)
This study explores in-depth the perceptions and experiences of employees at Toko Semat Sari Badung, a grocery store located at Jalan Semat Sari No. 3A, Tibubeneng Village, North Kuta, Badung, regarding the factors that drive their job satisfaction. Adopting a qualitative approach, data were collected through in-depth interviews with employees and the store owner, then analyzed thematically to uncover the meaning behind their narratives regarding salary, bonuses, working conditions, and relationships with coworkers. The findings indicate that while working conditions (the physical store environment) and relationships with coworkers (a sense of family) were consistently cited as highly significant sources of satisfaction and support, there were strong nuances of expectations regarding salary and bonuses. Employees perceived a gap between financial rewards and dedication, indicating a perception of fairness that management needs to address. Overall, this study reveals that job satisfaction at Toko Semat Sari Badung is the result of a complex interaction between a conducive physical environment, deep social support, and dynamics of compensation perceptions. Recommendations focus on open dialogue about compensation and strengthening appreciation, as well as ongoing efforts to foster a supportive work culture. Keywords: satisfaction, employee perception, human resource management